Modulation of Fatty Acid Composition of Aspergillus oryzae in Response to Ethanol Stress - Ma, Long (Microorganisms, 2019)
The koji mold Aspergillus oryzae is widely adopted for producing rice wine, wherein koji mold saccharifies rice starch and sake yeast ferments glucose to ethanol. During rice wine brewing, the accumulating ethanol becomes a major source of stress for A. oryzae, and there is a decline in hydrolysis efficiency. However, the protective mechanisms of A. oryzae against ethanol stress are poorly understood. In the present study, we demonstrate that ethanol adversity caused a significant inhibition of mycelium growth and conidia formation in A. oryzae, and this suppressive effect increased with ethanol concentration. Transmission electron microscopy analysis revealed that ethanol uptake triggered internal cellular perturbations, such as irregular nuclei and the aggregation of scattered vacuoles in A. oryzae cells. Metabolic analysis uncovered an increase in fatty acid unsaturation under high ethanol conditions, in which a large proportion of stearic acid was converted into linoleic acid, and the expression of related fatty acid desaturases was activated. Our results therefore improve the understanding of ethanol adaptation mechanisms in A. oryzae and offer target genes for ethanol tolerance enhancement via genetic engineering.